Immunoglobulin heavy chain/light chain pair measurement is associated with survival in diffuse large B-cell lymphoma. Issue 9 (September 2013) - Jardin, Fabrice; Delfau-Larue, Marie Hélène; Molina, Thierry Jo; Copie-Bergman, Christiane; Brière, Josette; Petrella, Tony; Canioni, Danielle; Fabiani, Bettina; Jais, Jean-Philippe; Figeac, Martin; Leroy, Karen; Mareschal, Sylvain; et al.
Abstract: Elevated serum free light chains (FLCs) have been associated with an unfavorable prognosis in diffuse large B-cell lymphoma (DLBCL). The aim of this study was to determine the clinical relevance of a quantitative assessment of intact circulating immunoglobulin (Ig), using serum Ig heavy chain/light chain pair (HLC) measurements in patients with DLBCL. FLC and HLC were measured in 409 serum samples of patients with DLBCL included in the LNH03-B clinical trial program of the Groupe d'Etudes des Lymphomes de l'Adulte (GELA). Patients with an abnormal IgMκ/IgMλ ratio or an abnormal FLC ratio more frequently displayed adverse clinical characteristics. Patients with abnormal IgMκ/IgMλ ratios had inferior progression-free survival (PFS) and overall survival (OS) as compared to patients with a normal ratio in the overall cohort (5-year PFS 44.9% vs. 69.3%, p = 0.0003 and 5-year OS 50.8% vs. 78.1%, p = 0.0003) and in the R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) cohort (5-year OS 43.5% vs. 70.3%, p = 0.003). In multivariate analysis, including elevated FLC/HLC and International Prognostic Index (IPI), an abnormal IgMκ/IgMλ ratio (hazard ratio [HR] = 1.54, 95% confidence interval [CI] 1.03–2.3, p = 0.03) remained predictive of shorter progression-free survival. Gene expression profile experiments and immunohistochemistry indicate that this measurement is at least partially related to tumor cell secretion. Both elevated serum FLCs and an abnormal IgMκ/IgMλ ratio are associated with unfavorable outcomes in patients with DLBCL treated by R-CHOP.